SOME OBSERVATIONS ON THE BREAK–EVEN CHART. - Patrick, A. W. (The Accounting Review, 1958)
Abstract The article presents observations of the author on a break-even Chart. The author believes that less emphasis should be placed on the specific break-even point and the attention should be on the probable profit or loss results of alternative courses of action. Break-even points are not necessary in arriving at intelligent decisions which involve cost-volume-profit relationships. Break-even points do exist and for this reason, it may be of academic interest to know what they are. But if they can be used, it is suggested that there is almost invariably a better approach to the problem. The author suggests that Break-even charts should be accompanied with detailed budgets and used with considerable caution only when the assumptions underlying the charts are thoroughly understood. Of more importance, however, is the placing of emphasis in planning on the relative profitability of alternative courses of action rather than the break-even point. The author concludes that to compute a break-even point, recognition of whether or not a knowledge of the point is pertinent to a decision faced by management and if it is pertinent, in what way is required.